Impact of Relative Humidity on Heat Stress Responses in Early-Lactation Holstein Cows - Janghoon Jo; Honggu Lee (Animals)
High relative humidity can increase the risk of heat stress in dairy cows, but its effects in humid continental climates are not well defined. This study evaluated how humidity levels influence dry matter intake, milk yield and composition, physiological response, blood hematology, metabolites, hormones, and heat shock protein gene expression in hair follicles. Sixteen multiparous early-lactating Holstein cows were assigned to four groups in a 2 × 2 factorial design with two temperatures (25 °C and 31 °C) and two humidity levels (50% (LRH) and 80% (HRH)). All cows were housed in climate-controlled chambers. Compared with LRH, HRH at both temperatures reduced dry matter intake, milk yield, milk fat, energy-corrected milk, and 3.5% fat-corrected milk. HRH also increased rectal temperature, heart rate, glucose, blood urea nitrogen, cortisol, and heat shock protein 90 in hair follicles. These results show that HRH, even at moderate temperature, affects dairy cow performance and alters physiological and metabolic functions. These findings emphasize the importance of precise management strategies to reduce the effects of humid heat stress on dairy performance. A comprehensive understanding of these responses is crucial for developing effective, sustainable solutions to ensure the viability of the dairy industry under increasing temperature and humidity.